Comparative analysis of poverty in Greece versus richer European Countries in the debt-crisis era - Georgios Symeonidis; Manolis Valavanis; Georgia Venetsanakou (Luxembourg Income Study (LIS), 2017)
This paper aims to analyze the impact of the reforms of the Greek Pension and Fiscal System on poverty, through a statistical analysis and to point out the changes in the main factors mentioned above and how they correlate. The analysis is achieved through the comparison of main identifiers between Greece and richer European countries. Firstly, the macroeconomic variables are presented. Then, the data analysis on income, income from pension and its correlation with owned housing is conducted and finally the reconstruction of poverty thresholds and its large variations are depicted, with an attempt to explain the differences based on methodological approach and data collection.
Keywords: 330